A study on factors affecting sales retention: Case study at Celcom Temerloh, Pahang / Siti Naquiah Othman - Othman, Siti Naquiah (2011)
The purposed of this study is to examine the factors affecting sales retention at Celcom Temerloh, Pahang. There are five factors that being studied, which were: customer service, customer loyalty, sales promotions and employees’ attitude. In collecting data, the researcher used both the secondary and primary data. Moreover, questionnaires had been used in order to get feedback from customers. The researcher had distributed 110 questionnaires to Celcom customers who were go to Celcom. The data collected was tested on its reliability, and then further analyzed using frequency analysis, descriptive mean tests and Regression Analysis. Meanwhile, Chi Square and Pearson Correlation Coefficient was used to test the hypotheses in this study. The findings of this research project recommend that all the factors are significant factors in explaining the determinants affecting sales retention at Celcom Temerloh. Based from the results obtained in this study, the researcher tries suggests some recommendations that can be used to help Celcom to improve their current strategies to increase the performance level in telecommunication industry to suit with their establishment